(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
New functionalized 2-imino-2,5-dihydrofuran has been synthesized by inter-action of 3-hydroxy-3-methylbutane-2-one with phenylhydrazide of cyanoacetic acid. Some chemical transformations have been carried out.